2022
DOI: 10.21307/ane-2021-026
|View full text |Cite
|
Sign up to set email alerts
|

Levels of happiness and depression in parents of children with autism spectrum disorder in Poland

Abstract: There are numerous factors that determine the sense of happiness and level of depression in caregivers of children with autism spectrum disorder (ASD). The aim of this paper is to evaluate happiness and depression in/among families with an ASD child and compare with families with neurotypical children. The study included 182 participants. The participants answered questions for two questionnaires:Beck Depression Inventory and Oxford Happiness Questionnaire. The outcome of the study identified significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…In addition, a previous study reported that depression affects subjective happiness [49]. Moreover, higher levels of depression decrease subjective happiness in caregivers [50]. In Spain, a study on subjective happiness and depression reported that subjective happiness is negatively correlated with depression; thus, with increased subjective happiness, the depression level decreases [51].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, a previous study reported that depression affects subjective happiness [49]. Moreover, higher levels of depression decrease subjective happiness in caregivers [50]. In Spain, a study on subjective happiness and depression reported that subjective happiness is negatively correlated with depression; thus, with increased subjective happiness, the depression level decreases [51].…”
Section: Discussionmentioning
confidence: 96%
“…The effects of having a child with disabilities were researched by Kostiukow, et al [33]. They compared parents of children with autism spectrum disorder of parents with normal development.…”
Section: Types Of Depressionmentioning
confidence: 99%
“…Depression and anxiety represent negative psychological constructs, and there are some studies that explore preventing or moderating them among the parents of children with ASD [ 12 , 13 ]. Happiness is recognized as a positive psychological construct, and some studies examined happiness among parents of children with ASD [ 14 , 15 ]. A recent Polish study reported that parents of children with ASD reported lower levels of happiness and higher levels of depression than parents of neurotypical children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Happiness is recognized as a positive psychological construct, and some studies examined happiness among parents of children with ASD [ 14 , 15 ]. A recent Polish study reported that parents of children with ASD reported lower levels of happiness and higher levels of depression than parents of neurotypical children [ 14 ]. There has been a growing belief that we should focus not only on preventing negative situations, such as depression, but also focus on positive aspects of life such as happiness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%